Abscopal effect of high-dose-rate brachytherapy on pelvic bone metastases from renal cell carcinoma: a case report - Suzuki, Gen; Masui, Koji; Yamazaki, Hideya; Takenaka, Tadashi; Asai, Syunsuke; Taniguchi, Hidefumi; Nakamura, Terukazu; Ukimura, Osamu; Yamada, Kei (Journal of Contemporary Brachytherapy, 2019)
Radiation therapy is considered an optimal partner for immunotherapies. Several pre-clinical studies have demonstrated that regression of distant metastases, at remote non-irradiated sites of the body, termed the “abscopal effect”, can be achieved by an appropriate timing and combination of radiation with immunotherapy. However, nearly all pre-clinical and clinical studies evaluating a combination of radiation and immunotherapies have used external beam radiation therapy. We present in this case report, the abscopal effect observed in a 30-year-old Japanese woman with metastatic renal cell carcinoma after the treatment with high-dose-rate interstitial brachytherapy combined with nivolumab. This is the first published report demonstrating an abscopal effect following brachytherapy for human malignancy. Our case indicates that immuno-oncology effects are not limited to external beam irradiation regimens as they can also be attained by brachytherapy.